Postnatal development of layer III pyramidal cells in the primary visual, inferior temporal, and prefrontal cortices of the marmoset - Aoi, Hirosato; Oga, Tomofumi; Sasaki, Tetsuya; Fujita, Ichiro; Ichinohe, Noritaka (Frontiers in Neural Circuits, 2013)
Abnormalities in the processes of the generation and/or pruning of dendritic spines have been implicated in several mental disorders including autism and schizophrenia. We have chosen to examine the common marmoset (Callithrix jacchus) as a primate model to explore the processes. As a first step, we studied the postnatal development of basal dendritic trees and spines of layer-III pyramidal cells in the primary visual sensory cortex (V1), a visual association cortex (inferior temporal area, TE), and a prefrontal cortex (area 12, PFC). Basal dendrites in all three areas were longer in adulthood compared with those in the newborn. In particular, rapid dendritic growth occurred in both TE and PFC around the second postnatal month. This early growth spurt resulted in much larger dendritic arbors in TE and PFC than in V1. The density of the spines along the dendrites peaked at 3 months of age and declined afterwards in all three areas: the degree of spine pruning being greater in V1 than in TE and PFC. The estimates of the total numbers of spines in the basal dendrites of a single pyramidal cell were larger in TE and PFC than in V1 throughout development and peaked around 3 months after birth in all three areas. These developmental profiles of spines and dendrites will help in determining assay points for the screening of molecules involved in spinogenesis and pruning in the marmoset cortex.